Early Islam Compensation: Pattern from Umar’s Caliphate and Learning for Human Resources Management - Rahmat, Ihsan; Kusuma, Bayu Mitra A.; Cahyadi, Ashadi; Handayani, Anis (International Journal of Economics, Management and Accounting, 2023)
One of the methods to reveal the concept of compensation in Islam is through historical legitimacy where the compensation narrative transformed along with improvement in Islamic governance. This study focused on uncovering the practices and basis for providing compensation during the time of Caliph Umar ibn Al-Khattab. Qualitative methodology was adopted by reviewing four major books as the main readings along with 17 other selected supporting articles. Tabulation was used to record the most significant contents to categorize based on the concept of direct and indirect compensation. This study found a variety of direct compensation practices such as the provision of salaries, benefits, and incentives. Indirect compensation includes provision of facilities, recognition, and prayers. This compensation is based on guidance of the Quran and the hadiths of Prophet Muhammad (sal-Allahu alayhi wa sallam). For an unprecedented condition, Umar took into consideration advice from senior friends either from their personal perspectives or experiences from other regions. The last is based on Umar’s ijtihad after analyzing the conditions. This study has implications for Islamic human resources management learning in modern organizations. Future researchers may examine the empirical significance of Umar’s compensation mechanism in modern organizations.